Trends in Research Related to Ophthalmic OCT Imaging From 2011 to 2020: A Bibliometric Analysis - Yu, Ziyan; Ye, Jie; Lu, Fan; Shen, Meixiao (Frontiers in Medicine, 2022)
Background: To explore hotspots and global research trends on Optical Coherence Tomography (OCT) in ophthalmic imaging field by using bibliometric technique. Methods: Documents related to OCT in ophthalmic imaging field between 2011 and 2020 were extracted from SCI Expanded database. Downloaded raw data was analyzed by VOSviewer and CiteSpace software. Bibliometric networks including publication number per year, countries, authors, journals, international collaborations and keywords were constructed. Results: 4,270 peer-reviewed documents were retrieved, and annual research output in the last ten years has increased significantly. The largest publishing country was the United States, and the most productive journal was Investigative Ophthalmology and Visual Science (IOVS). The most active academic institution was University of California Los Angeles, and the top rank publishing author was Duker JS. The most co-cited references mainly focused on new emerging OCT technique such as SD-OCT and OCTA. Conclusion: The bibliometric analysis of development trends in ophthalmic OCT imaging field on various aspects could provide developers or researchers with valuable information to propose future research directions and to seek further cooperation.